Pengaruh Etos Kerja Dan Disiplin Kerja Terhadap Prestasi Kerja Dengan Kepuasan Kerja Sebagai Variabel Intervening Pada PT. Hayati Pratama Mandiri Padang - Bayu Pratama Azka; Dori Mittra Candana; Ratih Purwasih (Riset Sinergi Indonesia, 2022)
This study aims to determine how much influence work ethic, work discipline, on job performance with job satisfaction as an intervening variable. The research variables are work ethic (X1), work discipline (X2), work performance (Y) and job satisfaction (Z). Methods of collecting data through surveys and distributing questionnaires to 82 respondents. The analytical method used is validity and reliability test, correlation analysis, multiple regression analysis, for hypothesis testing used t test and F test and path analysis. The results obtained show (a) there is a positive and significant effect on work ethic and on job satisfaction of 4.726 with a significant level of 0.000 <0.05 (b) there is a positive and significant influence on work discipline and on job satisfaction of 1.941 with a significant level of 0.056 < 0.05 (c) there is no positive and significant effect on work ethic and on work performance of 0.051 with a significant level of 0.959 > 0.05 (d) there is a positive and significant influence on work discipline and on work performance of 5.204 with a significant level of 0.000 < 0.05 (e) there is a positive and significant effect on job satisfaction and on work performance of 5.010 with a significant level of 0.003 < 0.05 (f) job satisfaction mediates the relationship between work ethic and work performance of 0.234 > 0.025 (g) job satisfaction mediates the relationship between work discipline and work performance by 0.220 > 0.096 Keywords: Leadership, Organizational Climate, Employee Performance and Job Satisfaction.